Persistent Increase in Serum 25-Hydroxyvitamin D Concentration in a Dog Following Cholecalciferol Intoxication - Gerhard, Charlotte; Jaffey, Jared A. (Frontiers in Veterinary Science, 2020)
Cholecalciferol is becoming an increasingly utilized rodenticide in the United States due to changes implemented by the Environmental Protection Agency (EPA) to reduce unintended exposure of wildlife to second-generation anticoagulant rodenticides. The lipophilic properties of cholecalciferol and prolonged tissue elimination are well-documented; however, long-term clinical ramifications are unknown. This report describes unique clinicopathologic and treatment features during the acute phase of cholecalciferol rodenticide toxicosis in a 4-year-old neutered Shih-Tzu mix that presented for intermittent vomiting, anorexia, polyuria, and polydipsia. In addition, this report also highlights the potential benefit of serial measurements of serum 25-hydroxyvitamin D concentrations and long-term treatment in the chronic phase of cholecalciferol rodenticide toxicosis in dogs.